Precursor Lesions of Cholangiocarcinoma: A Clinicopathologic Review - Bita Geramizadeh (SAGE Publishing, 2020)
Cholangiocarcinoma (CCA) develops through multistep carcinogenesis. During the past decades, 2 precursors have been proved to evolve to CCA. The 2 main precursor lesions of CCA are biliary intraepithelial neoplasia and intraductal papillary neoplasm of the bile duct. It is an interesting and relatively novel entity for the hepatobiliary surgeons, radiologists, oncologists, and pathologists. It worth being familiar with these 2 entities for better communication between pathologists, oncologists, and surgeons to improve the treatment and follow-up of these lesions, which can definitely decrease their evolvement to CCA as an aggressive, poor prognostic, and life-threatening cancer. In this narrative review, I collected and discussed all published studies about these 2 precursor lesions of CCA including radiologic, clinical, and pathological manifestation.